Resisting Dignity Takings in China - Pils, Eva (Law and Social Inquiry-Journal of the American Bar Foundation, 2016)
In the course of urbanization in the People's Republic of China, tens of millions of citizens have experienced expropriations of collectively owned land, expropriations of privately owned buildings, and evictions from urban land in state ownership. Summarily characterizing these measures as takings, I argue, first, that some takings observed have denied evictees dignity, understood as respect for their intrinsic moral worth and moral autonomy, in addition to dispossessing them of their land and homes. Second, in dignity takings, monetary compensation and resettlement schemes may fail to reflect the harm done to evictees by framing disputes over takings as (forced) economic bargains. Third, some victims unable to seek redress through judicial avenues have been driven into extrajudicial protest and resistance. In some cases, resistance can be restorative of dignity, but where repressive state responses to resistance prevent this potential from being realized, the injustice of dignity takings can be further aggravated.
CRIS-Team Scopus Importer:2023-03-21